(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The paper presents anatomical features of ocular motor nerves (cranial nerves III, IV, and VI). Vascular abnormalities are major causes of ocular motor abnormalities and include microvascular lesions, aneurysms of brain vessels, a pathology in the vertebrobasilar territory, brain neoplasms (particularly, those of the cerebellopontine angle, skull base and pituitary gland), and head trauma. Inflammation, myasthenia, endocrine ophthalmopathy, and demyelination are minor causes of ocular motor abnormalities. Ocular motor abnormalities should be differentiated from ocular motor lesions at the level of the medial longitudinal bundle such as internuclear ophthalmoplegia.